2021
DOI: 10.1111/ctr.14453
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery programs improve short‐term outcomes after liver transplantation–A systematic review and meta‐analysis

Abstract: This systematic review aimed to investigate the available quality of evidence (QOE) of enhanced recovery after surgery (ERAS) for liver transplantation (LT) on short-term outcomes, grade recommendations, and identify relevant components for ERAS protocols. A systematic review and meta-analysis were conducted on short-term outcomes after LT when applying comprehensive ERAS protocols (> 1 ERAS component) versus control groups (CRD42021210374), following the GRADE approach for grading QOE and strength of recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…They concluded that ERAS protocols in LT are related to improved short-term outcomes after LT with moderate to low quality of evidence and strong grade of recommendation. 63…”
Section: Liver Transplantation (Table 2)mentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that ERAS protocols in LT are related to improved short-term outcomes after LT with moderate to low quality of evidence and strong grade of recommendation. 63…”
Section: Liver Transplantation (Table 2)mentioning
confidence: 99%
“…DHOPE-DCD Trial -HOPE to prevent biliary complication post-LT: van Rijn, et al 58 HOPE (n = 78) led to a lower risk of nonanastomotic biliary strictures following LT with livers obtained from donors after circulatory death vs those from conventional static cold storage (n = 78) (6% vs 18%; RR .36). ERAS for LT: Tinguely, et al 63 ERAS protocols in LT led to decreased overall complications (OR .4) and decreased ICU and hospital length of stays. ERAS after LT is recommended (moderate to low quality of evidence; strong grade of recommendation).…”
Section: Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 7 of 391 patients (1.8%) required re-intubation. A recent systematic review investigated the quality of evidence for early extubation after LT as a part of an enhanced recovery after surgery (ERAS) project performed by the International Liver Transplantation Society (ILTS) [ 35 ]. They found that, overall, complications were reduced in the ERAS cohort versus controls (OR = 0.4 (CI 0.2, 0.7)), with no significant differences in mortality or hospital readmission rates.…”
Section: Mechanical Ventilation After Transplantationmentioning
confidence: 99%
“…Many factors can be classified as risk factors, include gender, APACHE score, average medical research council score, number of days of ICU stay and number of days of mechanical ventilation [6][7][8]. Early intervention of physical therapy and ERAS is highly recommended to avoid limitation in ADL activities and future disability [9][10][11][12][13][14][15]. However, no literature proves that on short-term ICU admission, especially those who underwent many procedures and was in ICU many times within short period in-between admissions.…”
Section: Introductionmentioning
confidence: 99%